Research methodologies in accounting and auditing: Empirical evidence from postgraduate projects concluded between 2008 and 2013 - Lopes, I. (Proceedings of the 13th European Conference on Research Methodology for Business and Management Studies ECRM 2014, 2014)
Research emerges as a continuous discovery and relates to knowledge creation and learning processes about physical and social world. These processes comprise a series of steps towards the final results achievements. This paper relates to the methodological matters and aims to identify the research approaches commonly used in the scientific field of accounting and auditing. Based on 258 postgraduate projects concluded between 2008 and 2013 and disseminated through the national scientific repository, we have explored those projects characteristics through a set of variables such as field of research, type of research, type of project, nature of higher education institution, methodological approach, and data sources, among other. Thus, we found several significant correlations between those variables which have permitted the identification of a research trend in accounting and auditing research. It would be expected that financial accounting follows a positive approach while management accounting follow an interpretative or critical approach, corroborating the literature on the topic. This insight was partially corroborated, associated with other key insights relating the current state of the art. Furthermore, evidence shows that higher education institutions, most of them listed in international rankings, tend to implement positivist approaches and use databases or inquiries as the main sources of primary data collection.